Implementasi Aplikasi Mobile Peta NKRI (Negara Kesatuan Republik Indonesia) Berbasis Android Menggunakan Metode Prototype - Adika May Sari; Desri Yani; Desy Suryani (Journal of Information System Research (JOSH), 2021)
Android technology is developing very rapidly, it is proven that everything can be done easily. Indonesia is the largest archipelagic country in the world. The alternative name for Indonesia is called Nusantara. With its many islands, Indonesia has 34 provinces. Therefore, the author makes an android-based application program about the map of the State of Indonesia. Where the method used is the prototype method. With Android studio programming language. This mobile application makes it easy for users to view a map of the Indonesian archipelago which consists of 34 provinces. This application is intended for school students, but ordinary people can also use it. In the past we could only see maps of the islands and provinces using books. With the development of mobile applications, an Android-based application for the NKRI map was made. In this application, users can view a map of Indonesia, and can use other features such as interactive games, questions about the map of Indonesia to add insight into the map of Indonesia